The interplay between competitive advantage and innovation in the MICE industry: a bibliometric and systematic review - Olivia, Putri Sarah; Purwana, Dedi; Wahono, Puji; Saparuddin, Saparuddin (Journal of Industrial Engineering & Management Research, 2024)
Maintaining a competitive edge through innovation has become crucial in the Meetings, Incentives, Conferences, and Exhibitions (MICE) industry given the rapid changes in global markets and technology breakthroughs. The relationship between innovation and competitive advantage in the MICE industry is examined in this systematic study, which employs the PRISMA technique to examine material from 2014 to 2024. The review delineates the fundamental concepts and dimensions of innovation and competitive advantage that are particular to the MICE industry, accentuating tactical methodologies and technical breakthroughs that bolster market standing and operational efficiency. Gained insights highlight how important innovation is to competitiveness and sustainable growth in a market that is becoming more complicated and environmentally concerned.